PERLINDUNGAN DATA PRIBADI KONSUMEN TERHADAP SISTEM LOCATION BASED ADVERTISING (LBA) OLEH PROVIDER TELEKOMUNIKASI - Alivia Putri Aina (2022)
Advances in technology affect many aspects of everyday life. One of the products resulting from technological developments is the creation of a means of activity for business actors to market their products or services more effectively and efficiently. Location-Based Advertising (LBA) is one of the advertising options in mobile advertising where actors can carry out promotions according to their desired targets because in their use LBA requires the location of the cellular card user. In addition to various advantages and conveniences for business actors in marketing activities, it turns out that LBA also has negative impacts such as the use of personal data of cellular card users (consumers) that are used without the consent of the data owner and the sending of LBA which is considered disturbing because of the sudden delivery. arrive. This study uses a normative legal research method using a statute approach and a comparative approach, which are sourced from library research and questionnaires via google forms which are distributed to cellular card users (consumers). The results of this study discuss how the protection of personal data of cellular card users with the Location Based Advertising (LBA) system and solutions related to the protection of personal data of cellular card users with the Location Based Advertising (LBA) system. As well as comparing the legal regulations governing personal data protection in the European Union, namely the General Data Protection Regulation (GDPR) and the Personal Data Protection Bill (RUU PDP) in Indonesia. Key Words : Location Based Advertising, Legal Protection, Personal Data